Complete Chloroplast Genome of the Inverted Repeat-Lacking Species Vicia bungei and Development of Polymorphic Simple Sequence Repeat Markers - Jo, Ick-Hyun; Han, Seahee; Shim, Donghwan; Ryu, Hojin; Hyun, Tae Kyung; Lee, Yi; Kim, Daeil; So, Yoon-Sup; Chung, Jong-Wook (Frontiers in Plant Science, 2022)
Background: Vicia bungei is an economically important forage crop in Korea and China. Although detailed genetic and genomic data can improve population genetic studies, conservation efforts, and improved breeding of crops, few such data are available for Vicia species in general and none at all for V. bungei. Therefore, the main objectives of this study were to sequence, assemble, and annotate V. bungei chloroplast genome and to identify simple sequence repeats (SSRs) as polymorphic genetic markers. Results: The whole-genome sequence of V. bungei was generated using an Illumina MiSeq platform. De novo assembly of complete chloroplast genome sequences was performed for the low-coverage sequence using CLC Genome Assembler with a 200–600-bp overlap size. Vicia bungei chloroplast genome was 130,796-bp long. The genome lacked an inverted repeat unit and thus resembled those of species in the inverted repeat-lacking clade within Fabaceae. Genome annotation using Dual OrganellarGenoMe Annotator (DOGMA) identified 107 genes, comprising 75 protein-coding, 28 transfer RNA, and 4 ribosomal RNA genes. In total, 432 SSRs were detected in V. bungei chloroplast genome, including 64 mononucleotides, 14 dinucleotides, 5 trinucleotides, 4 tetranucleotides, 233 pentanucleotides, 90 hexanucleotides, and 14 complex repeated motifs. These were used to develop 232 novel chloroplast SSR markers, 39 of which were chosen at random to test amplification and genetic diversity in Vicia species (20 accessions from seven species). The unweighted pair group method with arithmetic mean cluster analysis identified seven clusters at the interspecies level and intraspecific differences within clusters. Conclusions: The complete chloroplast genome sequence of V. bungei was determined. This reference genome should facilitate chloroplast resequencing and future searches for additional genetic markers using population samples. The novel chloroplast genome resources and SSR markers will greatly contribute to the conservation of the genus Vicia and facilitate genetic and evolutionary studies of this genus and of other higher plants.